2020
DOI: 10.1038/s41467-019-14140-y
|View full text |Cite
|
Sign up to set email alerts
|

Tree species traits affect which natural enemies drive the Janzen-Connell effect in a temperate forest

Abstract: A prominent tree species coexistence mechanism suggests host-specific natural enemies inhibit seedling recruitment at high conspecific density (negative conspecific density dependence). Natural-enemy-mediated conspecific density dependence affects numerous tree populations, but its strength varies substantially among species. Understanding how conspecific density dependence varies with species' traits and influences the dynamics of whole communities remains a challenge. Using a three-year manipulative communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
84
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 63 publications
9
84
1
2
Order By: Relevance
“…such as insect herbivores (Jia et al, 2020), and soil and fungal pathogens (Bagchi et al, 2010;Mangan et al, 2010). Evidence of C-NDD has been reported globally (Carson et al, 2008;Comita et al, 2014), with a variety of observational, experimental, and modeling approaches linking pathogen-induced C-NDD to the enhancement of plant community diversity (Bagchi et al, 2011;Harms et al, 2000;.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…such as insect herbivores (Jia et al, 2020), and soil and fungal pathogens (Bagchi et al, 2010;Mangan et al, 2010). Evidence of C-NDD has been reported globally (Carson et al, 2008;Comita et al, 2014), with a variety of observational, experimental, and modeling approaches linking pathogen-induced C-NDD to the enhancement of plant community diversity (Bagchi et al, 2011;Harms et al, 2000;.…”
mentioning
confidence: 99%
“…Species life-history strategies also affect the strength of C-NDD (Jia et al, 2020), with trade-offs between axes of growth and defence, at least partly, governing variation in species susceptibility of pathogens (Milici et al, 2020;Spear et al, 2015), potentially influencing seedling recruitment patterns. Shade-tolerant species are more susceptible to fungal pathogens (Kobe & Vriesendorp, 2011;McCarthy-Neumann & Kobe, 2008), particularly in fragmented forests .…”
mentioning
confidence: 99%
“…Such an influence of soil microorganisms on seedling density has been proved in many previous studies [3,8]. For example, plant-related fungi reduce the recruitment of seedlings in the vicinity of adult conspecifics in temperate humid forests [8].…”
Section: Introductionmentioning
confidence: 77%
“…Compounding this problem is experimental evidence that several distinct mechanisms can generate CNDD, including host‐specific pathogens or insects and intraspecific competition (Mangan et al 2010, McCarthy‐Neumann and Kobe 2010, Bagchi et al 2014, Jia et al 2020). The relative importance of these mechanisms also differs among species (Jia et al 2020), meaning that even a carefully designed study examining one or a few mechanisms, while valuable, would nonetheless fail to detect CNDD caused by other mechanisms. This is problematic because population and community dynamics will ultimately be influenced by differences in CNDD across localities and species regardless of the specific mechanisms generating that CNDD (Chesson 2000, Levine and HilleRisLambers 2009, HilleRisLambers et al 2012).…”
Section: Toward a Roadmap For Future Studiesmentioning
confidence: 99%
“…A productive way forward will be to integrate mechanism‐based and pattern‐based approaches. Specifically, we propose a two‐pronged approach: (1) test for phenomenological patterns predicted by CNDD at different scales of biological organization (individual growth and mortality, population vital rates, community dynamics) and then (2) explore mechanisms underlying those patterns using experimental studies of competition and natural enemies that have the potential to be geographically replicated (e.g., Forrister et al 2019, Jia et al 2020). For example, phenomenological studies of CNDD in tropical forests have highlighted the importance of interacting species (Comita et al 2010, Usinowicz et al 2017, Johnson et al 2017), and mechanistic studies have shown that fungal pathogens and insects are likely to be a driving force behind these patterns (Mangan et al 2010, Bagchi et al 2014, Gripenberg et al 2019, Forrister et al 2019).…”
Section: Toward a Roadmap For Future Studiesmentioning
confidence: 99%